Awakened : a house of night novel - Cast, P. C.; Cast, Kristin (Cast, P. C. House of night, 2011)
Zoey has returned from the Otherworld to her rightful place as High Priestess at the House of Night. Her friends are just glad to have her back, but after losing her human consort, Heath, will Zoey--or her relationship with her super-hot Warrior, Stark--ever be the same?